Fictional Discourse Analysis of Ramifications of the British Cultural Fragmentation in Kazuo Ishiguro’s The Remains of the Day - Aldhafeeri, Hilalah Dughayyim (Forum for Linguistic Studies, 2025)
This study attempts to explore the theme of cultural fragmentation through pursuing its postmodern traits in Kazuo Ishiguro’s The Remains of the Day. It illuminates the authorial description of socio-cultural changes in British society at the prime of world postmodernism through the novel’s fictional discourse. The study’s objective is to explore the theme of cultural fragmentation as a tangible clue to postmodern transition in British society. The novel is a literary manifestation of the British disengagement with the past as well as entering a new postmodern era characterized by various social ramifications limited to rejection of meta-narratives, incorporation plurality of identities, globalization, and the inevitability of change. The study’s methodology will be an interpretation of cultural fragmentation through applying Mikhail Bakhtin’s concept of dialogic discourse. Therefore, three literary elements will be analyzed to explore the novel’s portrayal of these ramifications, namely, setting, the characters’ discourse and interpersonal social affairs, and the plot’s fictional discourse. The interpretation of the novel’s discourse depends on the narrative structure of the characters’ speech, reflecting the author’s implied voice in the text. The characters’ language is the explicit expression of cultural fragmentation, which exemplifies Ishiguro’s implicit voice about postmodern reality. The duality of the author’s and characters’ voices will be accentuated as a way of perceiving cultural fragmentation through the lens of discourse analysis. In so doing, the study highlights the contemporary postmodern cultural changes that affect people’s lives and language as they communicate with each other on the grounds of social interactions.